2015
DOI: 10.1149/2.0201509jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reheating Treatment on Oxygen-Reduction Activity and Stability of Zirconium Oxide-Based Electrocatalysts Prepared from Oxy-Zirconium Phthalocyanine for Polymer Electrolyte Fuel Cells

Abstract: Zirconium oxide-based electrocatalysts with multi-walled carbon nanotubes as electroconductive support (ZrC x N y O z /MWCNT) were prepared by oxidation of oxy-zirconium phthalocyanine under low oxygen partial pressure and examined as new non-platinum cathodes for polymer electrolyte fuel cells. The effect of reheating treatment of ZrC x N y O z /MWCNT in the temperature range from 900 to 1200 • C for 1 h under nitrogen atmosphere on the activity and stability of the oxygen-reduction reaction (ORR) was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In regards to the metal catalyst, platinum has been the most used metal in this type of fuel cells. Nevertheless, the scarcity and high cost of this metal is a hindrance, and new materials that decrease the cost without compromising the catalytic activity would be beneficial [20][21][22] . Therefore, binary and ternary Pt-alloys that exhibit a higher activity than Pt alone have been developed [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the metal catalyst, platinum has been the most used metal in this type of fuel cells. Nevertheless, the scarcity and high cost of this metal is a hindrance, and new materials that decrease the cost without compromising the catalytic activity would be beneficial [20][21][22] . Therefore, binary and ternary Pt-alloys that exhibit a higher activity than Pt alone have been developed [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…10 In order to increase the very low catalyst dispersion (i.e., the electrochemically active surface area per gram of catalyst) obtained with the above synthesis approaches, methods to synthesize highly dispersed Zr oxide nanoparticles supported on carbon black were investigated. 12,[17][18][19] For these materials, the ORR activity was correlated with synthesis-specific parameters, such as temperature, gas composition, and heat-treatment time during synthesis, 4,5,9,[20][21][22][23] but a systematic quantitative comparison of the effect of the synthesis conditions on the ORR activity has not yet been conducted and is subject of the present work.…”
mentioning
confidence: 99%
“…We already demonstrated that the reheating treatment was useful to increase the stability of the deposited carbon [6]. Therefore, at first we tried to prepare the nano-sized oxide-based particles with high dispersion.…”
Section: Ecs Transactionsmentioning
confidence: 99%